2020
DOI: 10.1111/ene.14608
|View full text |Cite
|
Sign up to set email alerts
|

The Framingham cardiovascular risk score and 5‐year progression of multiple sclerosis

Abstract: Background and purpose Cardiovascular risk factors and comorbidities can affect the prognosis of multiple sclerosis (MS). The Framingham risk score is an algorithm that can estimate the 10‐year risk of developing macrovascular disease. Our objectives were to evaluate the possible association between the Framingham risk score at baseline and MS relapses, disability, and disease‐modifying therapy (DMT) choices over a 5‐year follow‐up. Methods This is a retrospective cohort study including 251 MS subjects. At bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
1
34
1
Order By: Relevance
“…CVD10 can be calculated using the Framingham CVD Risk score. 4 Lactate dehydrogenase (LDH) is an important enzyme in the anaerobic metabolic pathway. This enzyme is present in plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…CVD10 can be calculated using the Framingham CVD Risk score. 4 Lactate dehydrogenase (LDH) is an important enzyme in the anaerobic metabolic pathway. This enzyme is present in plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…In one retrospective study of 251 MS subjects, a one-point increase in baseline Framingham cardiovascular risk score was associated with a 31% higher risk of relapse, 19% higher risk of reaching an EDSS score of 6.0, and 62% higher risk of DMT escalation over 5 years. 40 A recent study using postmortem whole-body autopsy to assess vascular disease burden suggested an excessive burden of cerebral small vessel disease in persons with MS compared to controls who died at younger ages of ⩽ 60 years. 41 In a population-based study in the United Kingdom, persons with MS were found to have higher rates of macrovascular events and associated mortality than matched controls, which was irrespective of age and not fully accounted for by traditional vascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…These publications reported associations between this score and increased disability, relapse rate, severity, course, and risk of escalation of disease-modifying treatment. 12,13 Framingham Risk Score is a combined tool of several risk factors, and a recent paper reported a significant association between having multiple risk factors combined and decreased CGM volume. 9 In addition, studies have shown that hypertension and dyslipidaemia are also associated with decreased CGMvolume.…”
Section: Discussionmentioning
confidence: 99%
“…It combines individual cardiovascular risk factors into one outcome measure that has been associated with MS disability, relapse rate, severity, course, and risk of escalation of diseasemodifying treatment. [11][12][13] A relatively new way of determining disability is by assessing the agerelated MS severity (ARMSS) score. It ranks scores from the Expanded Disability Status Scale based on age at the time of assessment, thereby enabling comparison of disability across ages.…”
Section: Introductionmentioning
confidence: 99%